Insider Trading: Law of the Republic of Indonesia Number 8 of 1995 on Capital Market from Typewriters to Digital Era - Suwinto Johan; Ariawan Ariawan; Luo Yuan Yuan (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: Symmetric information is an essential factor in the capital market. Symmetric information will create an efficient capital market. Insider trading is one of the things that makes asymmetric information. The regulations on the capital market determine the criteria for insider trading. Insider trading is people who have non-public information on the company and earn financial benefits from non-public information.Purpose/Objective Study: This research aims to determine the insider trading criteria on the Indonesian Capital Market Law Number 8 of 1995.Design/Methodology/Approach: This research uses the normative juridical method. The study utilizes several cases that occur in countries as a discussion.Findings: This research concludes that the definition of insider trading consists of stakeholders who have interests and non-public information on public companies. The scope of insider trading is also extended to family members of stakeholders. Stakeholders include management, related companies' employees, officials, suppliers, shareholders, and their family members. The definition of family members is the spouse, children, and parents. The definition of insider trading should be extended to the current regulations. The related individuals must carry out the obligation to report share ownership.Paper Type: Research Article